PENGAMALAN KEAGAMAAN DALAM KEHIDUPAN MASYARAKAT DI DS. CIKADU KEC. SINDANGKERTA KAB. BANDUNG BARAT - Awan Gunawan (Jurnal Al Maesarah, 2023)
This study explains the practice of Islamic religious teachings in everyday life in Ds. Cikadu Kec. Sindangkerta Regency. West Bandung and what factors can manifest the practice of Islamic teachings in that community. It was found that religious practice in the community was going quite well, this was caused by several factors, namely the existence of the Islamic boarding school tradition that was embedded and manifested in religious life in society, which occurred due to religious activities such as teaching or ta'lim regarding science, knowledge, religious understanding and practice in several Islamic Boarding Schools and Majlis Ta'lim in Ds. Cikadu Kec. Sindangkerta Regency. West Bandung, so that people's lives are closely related to Islamic values.